Out of Communal Land: Clientelism through Delegation of Agricultural Tenancy Contracts - Takashi Kurosaki; Saumik Paul; Firman Witoelar (Institute of Labor Economics (IZA), 2021)
Do local institutions influence the nature of political clientelist exchange? We find a positive answer in the context of a village institution prevalent in Java since the Dutch colonial rule, where democratically elected village heads receive usufruct rights over a piece of communal village land (bengkok land) as a compensation for their service in lieu of salary. To formulate how limited-term private ownership of bengkok land promotes clientelism, we model a timely delegation of agricultural tenancy contracts to villagers-cum-voters as an incumbent re-election strategy. Based on a household survey fielded in 2018 across 130 villages in Java, Indonesia, we find that the chances of a bengkok plot being rented out increase by 6 percentage points as the time of the next election becomes closer by one year, and sharecropping is preferred to a fixed-rental contract as the election approaches. The empirical results are statistically significant and remain largely unchanged against a series of robustness checks. We also find suggestive evidence of short-term efficiency loss from clientelist politics over bengkok land.
Keywords: D72; H77; H83; O17; O18; 330; tanah bengkok; political budget cycle; clientelism; agricultural tenancy; electoral competition; Indonesia